Relationships among students’ reading habits, study skills, and academic achievement in English at the secondary level - Abid, Nisar; Aslam, Sarfraz; Alghamdi, Abdulelah A.; Kumar, Tribhuwan (Frontiers in Psychology, 2023)
Introduction Reading is an attempt to comprehend the writer’s message for personal growth and success in the relevant fields. Thus, psychologists consider it a multifaceted cognitive process of constructing meanings from texts. The present study was conducted to determine the relationships among students’ reading habits, study skills, and academic achievement in English at the secondary level in Punjab, Pakistan. Methods The (n = 1614) students enrolled in the science section for the academic year 2019–2020 participated in this descriptive correlational survey, selected from 40 high schools in Lahore, Punjab, Pakistan, through a non-proportionate stratified random sampling technique. The Reading Habits Questionnaire (RHQ) and the Study Skills Scale (SSS) were used to collect data about students’ reading habits and study skills. At the same time, academic achievement was the students’ grades obtained in the ninth class in the subject of English that were determined by the Board of Intermediate and Secondary Education (BISE) Lahore in 2019. Students’ responses were analyzed through descriptive and inferential statistics. Results The results indicated that students have competent reading habits and study skills. The correlational findings showed a strong positive relationship among reading habits, study skills, and academic achievement in English, while moderate positive relationships between reading habits and academic achievement in English. However, regression analysis results were significant, while reading habits and study skills moderately predicted academic achievement. Discussion It is implicated that teachers should plan such assignments and tasks based on reflective thinking by considering the role of study skills in academic achievement. Moreover, teachers and school administrators could mutually create timetables for library lessons to build reading habits and study skills among learners.